Differential effects of training on innovation. Issue 1 (2nd January 2023) - Cozzarin, Brian Paul; Percival, Jennifer C.
ABSTRACT: Evidence shows that training can increase product innovation. Yet in most studies survey design omits the differentiation between 'new' and 'improved' technical innovation. Thus, our objective is to quantify the impact of training on product and process innovation, especially in terms of new versus improved innovations. We use a national, establishment level, mandatory survey, explicity designed as longitudinal. We use a 2SLS approach to correct for endogeneity of training in the innovation production function. We find that training has no effect on new products, while it augments improved products. Training has a positive and significant effect on new and improved process innovations. A question that comes to mind is: 'Can we specifically train for new product innovation?' While there are highly cited papers in strategic management, we conclude after scanning the economics literature that a widely accepted theory of new product innovation does not exist. Perhaps, it is possible to train for new product innovation, while remaining cognizant of our inability to predict the recombinant knowledge required for newness. As Polanyi (1958. Personal Knowledge: Towards a Post-Critical Philosophy . University of Chicago Press) surmised: ' … invention must be acknowledged to be unpredictable, a quality which is assessed by the intensity of the surprise it might reasonably have aroused'.